The Challenges of Micro, Small and Medium Enterprises in Indonesia in the Era of the ASEAN Economic Community - Rina Shahriyani Shahrullah; Febri Jaya; Inal Arifin (Syiah Kuala Law Journal, 2021)
This study analyzes the challenges of Indonesian MSMEs under Law No. 20 of 2008 concerning Micro, Small and Medium Enterprises in the era of AEC 2015-2020 and the readiness of MSMEs under Law No.11 of 2020 concerning Job Creation (the Omnibus Law) in facing the era of AEC 2025. It adopted a normative legal research and found that MSMEs faced many challenges in the AEC era under the MSMEs Law. However, the amendment of this Law by the Omnibus Law constitutes a better strategy to improve and develop the Indonesian MSMEs to be ready in facing the AEC 2025.